Ratings and Cooperative Information Transmission - Martel, Jordan; Van Wesep, Edward Dickersin; Van Wesep, Robert (Management Science, 2022)
Researchers have often attributed discrete messages such as ratings to a difference in preferences between sender and receiver. By extending a standard model of information transmission, we show that discreteness can also arise when preferences are identical but misinterpretation is possible. Whereas discrete messages are less precise, they are easier to interpret. We provide predictions for the distribution of ratings. If we believe that an observed distribution results from cooperative behavior, the model provides a method for inferring the objectives of the sender and receiver. Ratings inflation and deflation arise as emergent properties of an optimal distribution. This paper was accepted by Gustavo Manso, finance. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2022.4297 .